(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of intensity-modulated radiotherapy (IMRT) combined with concurrent Paclitaxel - Carboplatin (PC) chemotherapy in patients with upper-third esophageal cancer (EC) at Nghe An Oncology Hospital. Subjects and Methods: A retrospective and prospective descriptive study was conducted on 32 patients with stage II-IVa upper-third esophageal cancer treated with IMRT and Paclitaxel - Carboplatin chemotherapy from January 2022 to June 2026. Post-treatment response was evaluated based on the RECIST 1.1 criteria. Early toxicities and adverse effects were assessed using the CTCAE v5.0 criteria. Results: Dysphagia symptoms improved in 78.1% of the patients. The treatment responses were as follows: complete response (CR) in 18.8%, partial response (PR) in 59.4%, stable disease (SD) in 12.5%, and progressive disease (PD) in 9.4%. There were statistically significant differences in response rates according to T stage, and overall disease stage (p < 0.05). Early adverse effects were predominantly Grade 1-2, including dermatitis (59.4%), esophagitis (84.4%), decreased hemoglobin (18.8%), and neutropenia (15.6%). Conclusion: The IMRT technique combined with the Paclitaxel - Carboplatin regimen for patients with upper-third esophageal cancer demonstrates high clinical and subclinical responses, with low and manageable adverse effects.